Oaths and Swearing in Ancient Greece - Sommerstein, Alan H. (De Gruyter, 2014)
The oath was an institution of fundamental importance across a wide range of social interactions throughout the ancient Greek world, making a crucial contribution to social stability and harmony; yet there has been no comprehensive, dedicated scholarly study of the subject for over a century. This volume of a two-volume study explores the nature of oaths as Greeks perceived it, the ways in which they were used (and sometimes abused) in Greek life and literature, and their inherent binding power.